Ketamine and serotonergic psychedelics: An update on the mechanisms and biosignatures underlying rapid-acting antidepressant treatment. (15th March 2023) - Johnston, Jenessa N.; Kadriu, Bashkim; Allen, Josh; Gilbert, Jessica R.; Henter, Ioline D.; Zarate, Carlos A.
Abstract: The discovery of ketamine as a rapid-acting antidepressant spurred significant research to understand its underlying mechanisms of action and to identify other novel compounds that may act similarly. Serotonergic psychedelics (SPs) have shown initial promise in treating depression, though the challenge of conducting randomized controlled trials with SPs and the necessity of long-term clinical observation are important limitations. This review summarizes the similarities and differences between the psychoactive effects associated with both ketamine and SPs and the mechanisms of action of these compounds, with a focus on the monoaminergic, glutamatergic, gamma-aminobutyric acid (GABA)-ergic, opioid, and inflammatory systems. Both molecular and neuroimaging aspects are considered. While their main mechanisms of action differ—SPs increase serotonergic signaling while ketamine is a glutamatergic modulator—evidence suggests that the downstream mechanisms of action of both ketamine and SPs include mechanistic target of rapamycin complex 1 (mTORC1) signaling and downstream GABAA receptor activity. The similarities in downstream mechanisms may explain why ketamine, and potentially SPs, exert rapid-acting antidepressant effects. However, research on SPs is still in its infancy compared to the ongoing research that has been conducted with ketamine. For both therapeutics, issues with regulation and proper controls should be addressed before more widespread implementation. This article is part of the Special Issue on "Ketamine and its Metabolites". Highlights: Ketamine and psychedelics have different initial mechanisms of action. Parallel downstream mechanisms may account for therapeutic similarities. Monoamines, opioid and sigma receptors, and inflammation are all promising targets. More research on psychedelics is needed compared to ketamine. Consideration of regulatory issues is crucial to implementation.